Meta-analysis of the Effect of Garlic on Microbial Count in Meat Products - Ramadani, Suci Putri; Kusumaningrum, Harsi D.; Hasanah, Uswatun (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2025)
Garlic (Allium sativum L.) is a natural ingredient used for microbiological control in meat products. This study aimed to analyze the effect of garlic addition on microbial count reduction in meat products through meta-analysis. The meta-analysis was conducted using 304 extracted data points from 10 articles, analyzed with the Hedges' d method. The results showed that the addition of garlic significantly reduced microbial counts (p<0.05) in three types of meat products: raw meatballs (minced mutton), ground beef, and raw chicken meat. Among the different forms of garlic tested, freeze-dried powder, oven-dried powder, and microencapsulated essential oil were the most effective in reducing microbial counts. Garlic treatment led to a reduction in seven types of tested microbes, except for Staphylococcus aureus. The highest microbial reductions were observed for Listeria monocytogenes (-6.626 to -2.009 log₁₀ CFU/g), sulfite-reducing anaerobes (-4.521 to -2.193 log₁₀ CFU/g), and Escherichia coli (-2.771 to -1.225 log₁₀ CFU/g).